PENINGKATAN HASIL BELAJAR IPA MELALUI PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NHT DI KELAS IV SD NEGERI 031 PULAU KIJANG - Rabiah Rabiah (JURNAL PAJAR (Pendidikan dan Pengajaran), 2018)
This research background from the learning result of natural science student of class IV SD Negeri 031 PulauKijang which still very low. This study aims to improve the learning outcomes of natural science. This study usesa classroom action research, consisting of 2 cycles. From the data analysis, there is an increase of both teacheractivity, student activity, and student learning result, that is teacher activity in meeting 1 cycle I got 56%(enough) and at second meeting it increased to 72% (good). In the second cycle of the third meeting the value ofteacher activity increased again to 80% (good) and at the fourth meeting increased to 88% (very good). Judgingfrom the activity of students also experienced an increase from 60% (enough) to 68% (good). In the second cycleof the third meeting to 80% (good) and at the fourth meeting increased to 92% (very good). Judging from theresults of the students also experienced preningkat, from the average score of students on the basic score is 62.after the first cycle the average score of students increased to 69 with an increase of 7 points from the basicscore. In the second cycle, the students' learning outcomes also increased by 7 points from cycle I with thestudent's average score of 76. It can be concluded that the advancement model of NHT can improve the learningoutcomes of the fourth grade students of SD Negeri 031 Pulau Kijang.